2014
DOI: 10.1182/blood-2013-08-523035
|View full text |Cite
|
Sign up to set email alerts
|

TTT-3002 is a novel FLT3 tyrosine kinase inhibitor with activity against FLT3-associated leukemias in vitro and in vivo

Abstract: Key Points• A novel TKI is discovered with potent and selective activity against FLT3-mutant cell lines and primary patient samples.• TTT-3002 is effective in vivo in several mouse tumor models of FLT3/ITDassociated AML with minimal toxicity.More than 35% of acute myeloid leukemia (AML) patients harbor a constitutively activating mutation in FMS-like tyrosine kinase-3 (FLT3). The most common type, internal tandem duplication (ITD), confers poor prognosis. We report for the first time on TTT-3002, a tyrosine ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…These include the protective effects of stromal niche cells (41), increased levels and activity of FLT3 ligand on FLT3 TK (15,17), trans-phosphorylation and increased activity of FLT3 by other kinases such as PIM-1 and SYK (42,43), and the collateral dependency on other important pro-growth and pro-survival signaling mechanisms (5,6,12,13). Other studies have focused on developing selective and more potent FLT3-TKI to overcome primary resistance to the first and second generation FLT3-TKI already in the clinic (44,45). Here, we document for the first time that co-treatment with the BET protein antagonist (BA) JQ1 and FLT3 inhibitor quizartinib or ponatinib synergistically induced apoptosis of not only cultured but also of the primary AML BPCs expressing FLT3-ITD.…”
Section: Discussionmentioning
confidence: 99%
“…These include the protective effects of stromal niche cells (41), increased levels and activity of FLT3 ligand on FLT3 TK (15,17), trans-phosphorylation and increased activity of FLT3 by other kinases such as PIM-1 and SYK (42,43), and the collateral dependency on other important pro-growth and pro-survival signaling mechanisms (5,6,12,13). Other studies have focused on developing selective and more potent FLT3-TKI to overcome primary resistance to the first and second generation FLT3-TKI already in the clinic (44,45). Here, we document for the first time that co-treatment with the BET protein antagonist (BA) JQ1 and FLT3 inhibitor quizartinib or ponatinib synergistically induced apoptosis of not only cultured but also of the primary AML BPCs expressing FLT3-ITD.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] For details on transplantation, drug administration, and experimental analysis, see supplemental Methods (available on the Blood Web site).…”
Section: Transplantation Experimentsmentioning
confidence: 99%
“…Cells were cultured in the presence of inhibitor for 1 hour at 37°C, and FLT3 and phospho-FLT3 expression was analyzed by performing immunoprecipitation of whole cell extracts for FLT3 (S-18), followed by SDS-PAGE and Western blotting as described previously (24). Other proteins were detected from whole cell lysates using the indicated antibodies and a horseradish peroxidase conjugated goat anti-rabbit secondary antibody followed by ECL.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that TTT-3002 is the most potent FLT3 inhibitor discovered to date, with picomolar IC 50 values against FLT3/ITD phosphorylation (24). Here we assess the activity of TTT-3002 against a broad spectrum of known FLT3/PMs, as well as a number of TKI resistance mutations within the FLT3/ITD allele.…”
Section: Introductionmentioning
confidence: 99%